(untitled) (Al-Farooq Journal of Sciences, 2026)
This study investigates the role of academics in narrowing the gap between accounting education and labour-market requirements by examining four interrelated dimensions: curriculum relevance, systematic identification of labour-market needs, practical training as a graduation requirement, and continuing professional development for academic staff. A descriptive-analytical approach was adopted, and a questionnaire was administered to a sample of 35 academic staff members from the Accounting and Banking and Finance Departments at the Faculty of Accounting, Gharyan University. Data were analysed using SPSS version 26 through Cronbach’s alpha, descriptive statistics, and a one-sample t-test. The findings indicate a generally low level of academics’ contribution to narrowing the gap, with an overall mean of 2.175. All four dimensions were rated at a low level. Labour-market needs assessment recorded the lowest mean (2.021), followed by practical training (2.000), while curriculum contribution recorded a mean of 2.443 and continuing professional development a mean of 2.234. The hypothesis tests were statistically significant for all dimensions at p<0.001, supporting the main hypothesis that academics do not currently play an effective role in narrowing the gap within the study setting. The findings are consistent with previous Libyan studies highlighting curriculum deficiencies and weak university–labour-market links, and with studies emphasizing the importance of practical training and professional skills development. The study’s contribution lies in moving beyond the general diagnosis of the accounting education gap to examine academics’ role through four connected institutional pathways within a specific Libyan university context. The study recommends periodic curriculum renewal, institutional mechanisms for monitoring labour-market needs, mandatory field training, and systematic professional development programmes for academic staff.